Consumer’s Personal Data Protection in the Digital Era - Hasnati, Hasnati; Seruni, Puti Mayang (Magister Hukum Universitas Semarang, 2024)
This research aimed to analyze the legislative arrangements related to the protection of personal data, especially for consumers. This research is important because it discusses the potential misuse of personal data belonging to consumers. The research was conducted normatively and analyzed qualitatively, and the results of this research on personal data protection in Indonesia are described descriptively. This research has resulted in new findings in the form of protection in the latest regulation and also challenges to enforce the regulation. So that these findings can be used as material for further research. The protection of personal data in Indonesia is regulated in several regulations. However, in 2022 Indonesia enacted Law number 27 of 2022 on the protection of personal data. This law contains specific norms regarding the right to protection of personal data from the limitation and definition of matters related to personal data, rights and obligations of subjects related to personal data to the regulation of sanctions. Currently, the protection of personal data, especially for consumers, still faces challenges, ranging from the challenge of low public awareness, standard clauses in consumer agreements to the absence of special institutions whose duties oversee the problems and implementation of data protection.